CyanoMetDB, a comprehensive public database of secondary metabolites from cyanobacteria. (15th May 2021) - Jones, Martin R.; Pinto, Ernani; Torres, Mariana A.; Dörr, Fabiane; Mazur-Marzec, Hanna; Szubert, Karolina; Tartaglione, Luciana; Dell'Aversano, Carmela; Miles, Christopher O.; Beach, Daniel G.; McCarron, Pearse; Sivonen, Kaarina; et al.
Highlights: Database 2010 secondary metabolites from cyanobacteria. Structural information (SMILES codes) provided for all compounds. Information aids analytical identification, research on biosynthesis and bioactivities. Applications as suspect lists in MS screening and for dereplication studies on natural products. Potential for open participation of research community for future editions of CyanoMetDB. Graphical abstract: Abstract: Harmful cyanobacterial blooms, which frequently contain toxic secondary metabolites, are reported in aquatic environments around the world. More than two thousand cyanobacterial secondary metabolites have been reported from diverse sources over the past fifty years. A comprehensive, publically-accessible database detailing these secondary metabolites would facilitate research into their occurrence, functions and toxicological risks. To address this need we created CyanoMetDB, a highly curated, flat-file, openly-accessible database of cyanobacterial secondary metabolites collated from 850 peer-reviewed articles published between 1967 and 2020. CyanoMetDB contains 2010 cyanobacterial metabolites and 99 structurally related compounds. This has nearly doubled the number of entries with complete literature metadata and structural composition information compared to previously available open access databases. The dataset includes microcytsins, cyanopeptolins, other depsipeptides, anabaenopeptins, microginins, aeruginosins, cyclamides, cryptophycins, saxitoxins, spumigins, microviridins, and anatoxins among other metabolite classes. A comprehensive database dedicated to cyanobacterial secondary metabolites facilitates: (1) the detection and dereplication of known cyanobacterial toxins and secondary metabolites; (2) the identification of novel natural products from cyanobacteria; (3) research on biosynthesis of cyanobacterial secondary metabolites, including substructure searches; and (4) the investigation of their abundance, persistence, and toxicity in natural environments.